Utilization Of Antenatal Care Services in The Gandhinagar (Rural) District, Gujarat - Patel, Vaibhavi D; Puwar, Bhavna T; Sheth, Jay K (National Journal of Community Medicine, 2013)
Back ground :Maternal and child health care is one of the eight essential components of primary health care as per Alma–Ata Declaration. Materials & Methods: A Multi-Indicator Cluster Survey (MICS) was conducted in April 2008 using 30 cluster technique. Results: 118 (7.82 %) women who were pregnant at the time of MICS survey were included in this article. More than half of the women were in 20 to 24 years age group with mean age 23.75 years. At the time survey 83% of the antenatal women had registered for Antenatal care and about two third of antenatal women had received IFA tablets, a single dose of TT injection and undergone BP measurement. About two third of the Antenatal women had registered for ANC at government health facilities and about one third at private hospital. Knowledge about the Chiranjeevi Yojana and JSY was very poor. 61% antenatal women had registered at Mamta session(VHND). The significant association was found between availing the ANC services and planning the institutional delivery.(p-0.009) Conclusions: Awareness about the government scheme for delivery was very low. ANC visits are opportunity for counseling the women for institutional delivery.